Do non-intermediation services tell us more in the finance–growth nexus?: causality evidence from eight OECD countries. Issue 7 (7th February 2020) - Cheng, Su-Yin; Hou, Han
ABSTRACT: This paper provides new evidence on a traditional finance–growth nexus through dividing financial services into financial intermediation and non-intermediation services and examining their relationships with economic growth. Applying time-series cointegration techniques and Granger causality tests for eight Organization for Economic Cooperation and Development (OECD) countries, reveals several results. First, there is a long-run equilibrium relationship among economic growth, intermediation activities, and non-intermediation activities in Austria, France, and Korea. Second, non-intermediation services impede long-run economic growth in Austria and France, whereas non-intermediation business and financial intermediation services accelerate Korea's long-term growth. Third, weak exogeneity tests support long-run bi-directional causality and the supply-leading hypothesis in terms of the relationship between financial services and economic growth. Finally, the influences of intermediation and non-intermediation activities on economic growth vary across countries, financial services, and time periods, indicating that countries should adopt different financial services to enhance long- or short-term economic growth. This paper emphasizes the importance of non-intermediation activities in the growth process and in the development of intermediation services.